1995
DOI: 10.1364/josaa.12.000761
|View full text |Cite
|
Sign up to set email alerts
|

Phase shifting for nonsinusoidal waveforms with phase-shift errors

Abstract: In phase measurement systems that use phase-shifting techniques, phase errors that are due to nonsinusoidal waveforms can be minimized by applying synchronous phase-shifting algorithms with more than four samples. However, when the phase-shift calibration is inaccurate, these algorithms cannot eliminate the effects of nonsinusoidal characteristics. It is shown that, when a number of samples beyond one period of a waveform such as a fringe pattern are taken, phase errors that are due to the harmonic components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
83
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(85 citation statements)
references
References 11 publications
2
83
0
Order By: Relevance
“…These phase increments are generally applied using a piezoelectric device (PZT). Although three frames are normally sufficient to compute the phase distribution, the measurement process is sensitive to various systematic [6][7][8][9][10][11][12][13][14][15][16][17][18] and random errors [19][20][21][22][23][24]. The large number of frames has been shown to decrease the sensitivity to these errors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These phase increments are generally applied using a piezoelectric device (PZT). Although three frames are normally sufficient to compute the phase distribution, the measurement process is sensitive to various systematic [6][7][8][9][10][11][12][13][14][15][16][17][18] and random errors [19][20][21][22][23][24]. The large number of frames has been shown to decrease the sensitivity to these errors.…”
Section: Introductionmentioning
confidence: 99%
“…The algorithm proposed by Hibino et al [14] offers the possibility to reduce the calibration error in the presence of higher order harmonics. Hibino et al [14] and Surrel [11] showed that 3 2 + κ and 2 2 + κ samples are respectively necessary to minimize the effect of the th κ order harmonic, with the phase step ( )…”
Section: Introductionmentioning
confidence: 99%
“…The algorithm proposed by Hibino et al 5 offers the possibility of reducing calibration error in the presence of higher-order harmonics. Hibino et al 5 and Surrel 2 showed that kth-order harmonics can be minimized with phase step 2p͑͞k 1 2͒ between acquired data frames.The objective of this Letter is to propose a novel approach to obtaining phase measurements in the presence of PZT miscalibration and multiple-order harmonics in the sampled waveform. This method, which permits free choice of the phase shifts from 0 to p, completely avoids imposing conditions on the phase shift that must be applied by establishing a high-resolution technique 6 for estimating the phase step.…”
mentioning
confidence: 99%
“…The algorithm proposed by Hibino et al 5 offers the possibility of reducing calibration error in the presence of higher-order harmonics. Hibino et al 5 and Surrel 2 showed that kth-order harmonics can be minimized with phase step 2p͑͞k 1 2͒ between acquired data frames.…”
mentioning
confidence: 99%
See 1 more Smart Citation